2013
DOI: 10.3109/13880209.2013.833948
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic interaction and mode of action ofCitrus hystrixessential oil against bacteria causing periodontal diseases

Abstract: Context: Citrus hystrix de Candolle (Rutaceae), an edible plant regularly used as a food ingredient, possesses antibacterial activity, but there is no current data on the activity against bacteria causing periodontal diseases. Objective: C. hystrix essential oil from leaves and peel were investigated for antibiofilm formation and mode of action against bacteria causing periodontal diseases. Materials and methods: In vitro antibacterial and antibiofilm formation activities were determined by broth microdilution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 34 publications
1
17
0
Order By: Relevance
“…The better antimicrobial efficacy may be as a result of the mixture of chemically different biologically active compounds such as terpenes, both oxygenated and non-oxygenated [59]. Dinan et al [60] revealed that the mode of action of EOs takes place against microorganisms by attacking the microbial cell wall, which resulted in increased permeability and loss of cellular constituents, acidification of the cytoplasmic content; blocking the production of cellular energy and synthesis of structural components; and, finally, destruction of genetic material leading to the death of the microorganisms [61]. The synergistic activity of CEOs may be due to their actions on microbial cell membrane.…”
Section: Discussionmentioning
confidence: 99%
“…The better antimicrobial efficacy may be as a result of the mixture of chemically different biologically active compounds such as terpenes, both oxygenated and non-oxygenated [59]. Dinan et al [60] revealed that the mode of action of EOs takes place against microorganisms by attacking the microbial cell wall, which resulted in increased permeability and loss of cellular constituents, acidification of the cytoplasmic content; blocking the production of cellular energy and synthesis of structural components; and, finally, destruction of genetic material leading to the death of the microorganisms [61]. The synergistic activity of CEOs may be due to their actions on microbial cell membrane.…”
Section: Discussionmentioning
confidence: 99%
“…LC 50 of EO of Allium macrostemon (72.86 ppm) was better than a major constituent, methyl propyl disulfide (86.16ppm), while its efficacy was lower than the other major component, dimethyl trisulfide (36.36ppm), against Ae. albopictus (40).…”
Section: Discussionmentioning
confidence: 99%
“…Synergistic effects of constituents of some EOs are nowadays well-known when they are used as anti-fungal or anti-bacterial agents (39, 40). Our findings in this research and our previous study also show that An.…”
Section: Discussionmentioning
confidence: 99%
“…Cont. Table 1: Summary of plants screened for antibiotic modulatory effects of commercially available drugs against nosocomial bacteria, that yielded synergistic effects 32,45,[80][81][82][83][84][85] . is the author/funder, who has granted medRxiv a license to display the preprint in perpetuity.…”
Section: (Which Was Not Certified By Peer Review)mentioning
confidence: 99%